Mediating Role of Halal Technology Implementation on Halal Purchase Intention in Semarang - Savitri, Fania Mutiara; Perwita, Atika Dyah (International Journal Ihya' 'Ulum al-Din, 2020)
This study aimed to analyze halal purchase intention that is mediated by halal technology implementation on packaging product in Semarang City, Indonesia. This analysis tried to build the concept of consumer behavior based on Islamic branding technology. The research model was developed through research variables to fill existing research gap between halal awareness and halal purchase intention by halal technology implementation. This technology able to detect halal label validated by MUI that is expected to mediate both variable.Research approach used quantitative approach. Data was collected by survey questionnaire methods for packaging product’s consumer in Semarang. This research used purposive sampling to obtain 100 consumers as data observation. SEM analysis was used to analyze the data through running Smart PLS 3.2.8 for Professional application for hypothesis testing.The finding presented that Consumer Behavior based on Islamic Branding Technology Concept is proven. It is proved by significant mediating effect between halal awareness to halal purchase intention through halal technology implementation (0.016). Other result proved that halal awareness has insignificant value on halal purchase intention of packaging product in Semarang (0.412), halal awareness has significant value on halal technology implementation (0.000) and halal technology implementation has significant value on halal purchase intention (0.011).